The potential of biological sludge amended combustion coal ash residues as artificial plant growth media : a laboratory column study to assess the influence of weathering on elemental release - De Jager, Pieter Christiaan (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2012.